Unusual presentation of lung cancer: A case report - Pereira, Chirag; Tauro, Leo F (Indian Journal of Case Reports, 2020)
The most common presentation of lung cancer is a cough. Gastrointestinal metastasis of lung cancer is a rare presentation, but it is well documented in the literature with the small intestine being the most common site of metastasis. We report the case of a 67-year-old man, an undiagnosed case of lung cancer that presented to our emergency department with acute abdominal pain due to jejunal perforation.